An experimental study of dynamic jet behaviour in a scaled cold flow spray dryer model using PIV. (8th October 2014) - Pawar, Sandip K.; Abrahams, Ruud H. M.; Deen, Niels G.; Padding, Johan T.; van der Gulik, Gert‐Jan; Jongsma, Alfred; Innings, Fredrik; Kuipers, J. A. M. (Hans)
Abstract Research on the dynamic flow behaviour in spray dryers has a long history. Interest in describing these flows originates from problems like roof and wall fouling. The aim of the present study is to experimentally investigate the dynamic jet behaviour and turbulent flow in a scaled‐down cold flow model of a spray dryer in order to better understand and optimize spray drying units. Dynamic jet behaviour and turbulent flow features (i.e., RMS velocities) were studied by particle image velocimetry (PIV) using water as the continuous phase. To obtain more insight in the jet dynamics, we analyzed the turning point, the width and shape, and the velocity profiles of the turbulent jet at different heights and the turbulence characteristics. We found that at higher Reynolds numbers, the jet penetrates further along the downward direction with a time‐averaged profile which is symmetric at the centre. In addition, we investigated the effect of the expansion ratio via proper orthogonal decomposition (POD). Outcomes of different characteristics of the dynamic jet, like steady, transient, regular, and complex precession, can be collapsed by proper scaling. These results can be used for validation of computational fluid dynamics simulations and facilitate the design (identification of jet operation boundaries) of new spray dryer configurations.